Adsorption of alkenes on acidic zeolites. Theoretical study based on the electron charge density - Zalazar, Maria Fernanda (2009)
In the present work, experiments on electron density changes in the adsorption process of alkenes on acidic zeolites, in the framework of atoms in molecules theory (AIM), were carried out. Electron densities were obtained at MP2 and B3LYP levels using a 6-31++G(d,p) basis set. This study explores the energetic and the electron density redistributions associated with O-H⋯π interactions. The main purpose of this work is to provide an answer to the following questions: (a) Which and how large are the changes induced on the molecular electron distribution by the formation of adsorbed alkenes? (b) Can a reasonable estimate of the adsorption energy of alkenes on the active site of zeolite be solely calculated from an analysis of the electron densities? We have used topological parameters to determine the strength and nature of the interactions in the active site of the zeolite. All the results derived from the electron density analysis show that the stabilization of the adsorbed alkenes follows the order isobutene > trans-2-butene ≅ 1-butene ≅ propene > ethene, reflecting the order of basicity of C=C bonds, i.e., (Cter=Cprim) > (Csec=Csec) ≅ (Cprim=Csec) > (Cprim=C prim). In addition, we have found a useful set of topological parameters that are good for estimating the adsorption energy in adsorbed alkenes. © 2009 American Chemical Society.